PERAN PASTORAL KONSELING BAGI PEMUDA YANG MENGALAMI MASALAH FRESH GRADUATE SYNDROME SETELAH LULUS KULIAH - Ralendesang, Nivtrik Netson; Lombogia, Randy A.A. P. (PT. Giat Konseling Nusantara, 2024)
Fresh Graduate Syndrome is a term for young people who, when they graduate from college or education, experience stress problems with the uncertainty of the life they have to live. The life of having to choose what to do next, whether to work or not, and carrying out what things are the main elements in the problem of Fresh Graduate Syndrome. This research focuses on young people who have graduated from college and have to experience Fresh Graduate Syndrome. This research is qualitative with a descriptive method which describes the problems experienced by young people. Pastoral counseling services will be an effort to handle or assist the problems experienced by the youth.